Do Tax Incentives and Social Media Adoptions Affect on MSME Performance? The Moderation of Tax Digitalization - Giawan Nur Fitria; Rista Bintara; Nurul Hidayah (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This work investigates the effect of tax incentives and social media adoption on the MSME performance and evaluates whether tax digitalization moderates these relationships. Background Problems: Although governments have introduced various fiscal incentives and digital initiatives, MSME performance continues to vary considerably. Existing studies tend to analyze tax incentives, social media usage, and tax digitalization separately, offering limited insight into their combined effects and the contextual role of digital tax systems in supporting SME performance. Novelty: This study lies in its integrated framework that merged fiscal policy and digital marketing strategy while incorporating tax digitalization as a moderating variable, thereby extending the understanding of MSME performance in the digital economy. Research Methods: A quantitative research design is employed using primary data gathered from MSME owners through structured questionnaires. The hypotheses are tested using regression-based moderation analysis to examine both direct and interaction effects by SmartPLS 4. Results:The findings reveal that tax incentives and social media adoption enhence MSME performance. However, the effect of tax incentives and social media adoption on SME performance remains unaffected by tax digitalization. Conclusion: The study concludes that while tax incentives and digital marketing adoption are key drivers of SME performance Currently, tax digitalization is predominantly compliance-oriented and has not developed into a strategic resource capable of reinforcing the influence of fiscal policies and social media adoption on MSME performance.